PERANAN BADAN PERMUSYAWARATAN DESA DALAM PEMBENTUKAN PERATURAN DESA DI DESA BRAHU KECAMATAN SIMAN KABUPATEN PONOROGO - Sakila, Yola Cindytia; Madalina, Maria (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2020)
The research examines the role and the obstacles of village consultative council as patner of village head in establishing Village Regulation. This legal research is included in the type of empirical legal research. The approach used by the author is the qualitative approach. The legal sources used consist of primary legal material and secondary legal material. The technique of data collection is done by interviews and library research. The analysis technique used is qualitative data analysis. The result of the research shows that: (1) the role of the village consultative council in the formation of village regulations in Brahu Village, Siman District, Ponorogo Regency is not optimal enough to extend the hand of the village because the village regulations that have been estabilished in the past a year do not reflect the needs of the community and the community and the constrains effecting the legislative function of the village consultative council; (2) the factors that become obstacles in the preparation and stipulation of the protest, among other the poor quality performance of the village apparatus and village consultative bodies and the revised community in approving aspirations: (3) efforts to overcome them are provide legal drafting training to The Village Consultative Council and socialization to the public about The Village Consultative Council.